2017
DOI: 10.21533/pen.v5i2.107
|View full text |Cite
|
Sign up to set email alerts
|

Sovereign Wealth Funds: A Comparison of the Turkish Sovereign Wealth Fund with the World Samples

Abstract: Sovereign wealth funds represent unity of assets that are directly or indirectly under public control and whose investments are largely concentrated across borders. Strategic objectives of the sovereign wealth funds are accumulating income surpluses for future generations or restoring the economic order and stabilizing it over the years when volatility is intense. Turkey decided the establishment of sovereign wealth fund in 2016. In this study, firstly, information on the practices of sovereign wealth funds is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…World and domestic experience shows that for economic recovery in the country, along with investments in physical capital, large-scale investments in education, health [27], culture and other components of human capital are required, increasing confidence in the government, that is, increasing social capital. This tendency is illustrated in [11], where investments in social sphere increased approximately twice. In addition, Patnem, 1996 in [21] showed that the solution to many macroeconomic problems, such as poverty, high unemployment, and the development of education and healthcare, is more effective if public organizations and civil society institutions are involved, because in this case the implementation of social norms is stabilized.…”
Section: Introductionmentioning
confidence: 90%
“…World and domestic experience shows that for economic recovery in the country, along with investments in physical capital, large-scale investments in education, health [27], culture and other components of human capital are required, increasing confidence in the government, that is, increasing social capital. This tendency is illustrated in [11], where investments in social sphere increased approximately twice. In addition, Patnem, 1996 in [21] showed that the solution to many macroeconomic problems, such as poverty, high unemployment, and the development of education and healthcare, is more effective if public organizations and civil society institutions are involved, because in this case the implementation of social norms is stabilized.…”
Section: Introductionmentioning
confidence: 90%